Mandibular advancement with clear aligners in the treatment of skeletal Class II. A retrospective controlled study - Caruso, S; Nota, A; Severino, M; Gatto, R; Meuli, S; Mattei, A; Tecco, S (European journal of paediatric dentistry, 2021)
The current study aimed to analyse the dentoskeletal effects of the Invisalign mandibular advancement (MA) device in the treatment of skeletal Class II malocclusions. Pre-treatment and post-treatment lateral skull radiographs from patients treated with MA versus TB (Twin-Block Appliance) at the Department of Orthodontics of the University of L'Aquila, Italy, were traced. Eligibility criteria included SNB<78; ANB>4; no previous orthodontic treatments; and vertebral maturation stage (CVM) CS3. Radiographs from patients with craniofacial anomalies, or who underwent extraction treatments, were excluded. Totally, 20 patients were examined, 10 of whom treated with MA and 10 treated with TB. All the radiographs were traced by one expert operator, blind to the groups. A preliminary method error study was performed to exclude intra-operator differences. Baseline characteristics of the participants were similar between the groups. Both appliances demonstrated a reduction of SNB and ANB angle, and a decrease in overjet. TB demonstrated a higher efficacy in increasing mandibular dimensions. A significant retroinclination of the upper incisive was observed in the TB group, where a decrease of SNA angles was additionally observed. The resulting differences between the two groups could be attributed to the different design of the appliances. The present data show the effectiveness of both TB and MA in the management of skeletal Class II malocclusions due to mandibular retrusion. But some differences exist in the dentoalveolar effect of the two appliances. MA seems indicated in Class II cases where a control of the upper frontal teeth position is needed.